Demonstrating environmental impacts on the sound structure of languages: challenges and solutions - Maddieson, Ian; Benedict, Karl (Frontiers in Psychology, 2023)
Recent research has suggested that there are significant associations between aspects of the phonological properties of languages and the locations in which they are spoken. In this paper we outline a strategy for assembling maximally reliable and well documented climatic and environmental data to place in juxtaposition with carefully curated linguistic information on both language location and structure. Problems with temperature records are specifically highlighted as an illustration of the use of the platform and considerations when selecting environmental data for analytic use. Preliminary analyses suggest that certain previously proposed language-environment relationships are statistically valid, but that these may be better placed in a broader framework of language types.